ORDER OR CHAOS? ORIGIN AND MODE OF EMPLACEMENT OF BRECCIAS IN FLOORS OF LARGE IMPACT STRUCTURES - Dressler B.O.; Reimold W.U. (My University, 2004)
Breccias in the crater floor of large impact structures are pseudotachylites (sensu largo), authigenic monomict and polymict clastic-matrix breccias, so-called footwall breccias, and impact melt breccias. Pseudotachylite bodies in the center of large impact structures (e.g., Vredefort Dome, South Africa) appear to have a random distribution and orientation, but most dip steeply or vertically. Large bodies of pseudotachylite in the more distal sectors of the >200-km-diameter Sudbury Structure have been interpreted as ring and terrace collapse features. In the Vredefort Dome, networks of randomly distributed pseudotachylite veins accompany large (“mother lode”) pseudotachylite dikes. In general, pseudotachylites in the floors of central parts of impact craters may form through explosive transfer of thermal shock energy, in a process that could be termed “flash replacement melting”, whereas pseudotachylites at large distances from the centers of large impact structure are believed to have formed through friction leading to partial or complete melting, similar to the formation of tectonic pseudotachylites. In smaller structures (e.g., Ries and Slate Islands), clastic-matrix breccias instead of pseudotachylites occur as the most common breccias in the crater floors. They have a chaotic distribution pattern. Their dips are commonly also steep to vertical. Melt breccia dikes in the target rocks of the crater floor are associated with melt sheets that fill the lower part of the excavation cavity. At Vredefort, erosion has removed the coherent melt sheet, but melt breccia dikes (Vredefort Granophyre) in the crater floor are preserved. They are characterized by a remarkably homogeneous chemical composition and are believed to represent the initial, undifferentiated impact melt. Near the Vredefort collar, the Granophyre forms more or less concentric dikes. In the more central parts of the Dome, their orientation is more random, but, in places, may be controlled by the Archean fabric of the crater basement. The “Offset” dikes of the Sudbury Structure are associated with the Sudbury Igneous Complex that represents, in total or in part, a differentiated impact melt sheet. The dikes, in many aspects, are similar to Vredefort Granophyres, but their interpretation as undifferentiated bulk melt is problematic on geochemical and structural grounds. Chemically, these dikes are not homogeneous and, in places, they contain massive sulfide deposits that are unlikely components of an undifferentiated impact melt. Differentiation and precipitation of massive sulfides are slow processes compared with the presumably high energy and fast emplacement of a supposedly undifferentiated melt.Pseudotachylites of the central impact crater apparently are mainly produced in the compression phase of the impact process, whereas clastic-matrix breccias form during the uplift and crater modification phases. Impact melt breccia dikes contain pseudotachylite-bearing inclusions and cut across pseudotachylite bodies. Such impact melt breccia dikes were probably emplaced during uplift and crater modification.